Environmental dermatology in childhood: photosensitivity. Issue 6 (December 2008) - Horkay, Irene; Emri, Gabriella; Varga, Viktoria; Simics, Eniko; Remenyik, Eva
Recently, sunlight-induced damage of healthy human skin, including skin malignancies and a large scale of photodermatoses representing a diverse group of diseases, have increased in childhood as a result of unfavorable environmental changes. This article yields an overview of the diagnosis, the clinical features and the treatment of these conditions and disorders and also reveals perspectives. Some diseases are more frequent in the pediatric population than in adulthood, whereas others heal spontaneously during adolescence and vice versa. The majority of cases are idiopathic photodermatoses, mainly polymorphic light eruption. Photosensitivity may be an early symptom of genetic disorders, such as porphyria, or very rare genophotodermatoses. Photosensitivity, secondary to topical or systemic external agents as well as photoexacerbated dermatoses, is not so frequent in childhood. Effective photoprotection is crucial.